Essays on political economy - Canales, Diego (2021)
Typically, political phenomena have been the main focus of study for philosophers and political scientists. However, with the advent of mathematicians (e.g., Hotelling, Debreu, and Arrow) to the Economics discipline, there was an increased inclination to utilize advanced mathematical technique to solve complex problems around political science. This dissertation attempts to follow that tradition. In the next two chapters, we analyse political phenomena using economic tools.